Distribution of perfluoroalkyl compounds in Osaka Bay and coastal waters of Western Japan. (March 2017) - Beškoski, Vladimir P.; Yamamoto, Katsuya; Yamamoto, Atsushi; Okamura, Hideo; Hayashi, Mitsuru; Nakano, Takeshi; Matsumura, Chisato; Fukushi, Keiichi; Wada, Shinpei; Inui, Hideyuki
Abstract: Perfluoroalkyl acids (PFAAs) including perfluoroalkyl sulfonates (PFSAs) and perfluoroalkyl carboxylates (PFCAs) were analyzed in sediment samples taken from Ajifu Waterway in Osaka city, from Osaka Bay, and from Kagoshima Bay, as well as in fifteen seawater samples collected from Osaka Bay and coastal waters of Western Japan. In all sediment samples, only PFCAs were detected, and the highest concentration was determined in Ajifu Waterway, where ΣPFAA was 58990 ng kg −1 dry weight. The total concentrations of PFAAs in sea water samples ranged between the limit of quantification and 53.4 ng L −1, and perfluorohexanoic acid was the most prevalent and had the highest concentration of 37 ng L −1 . The changes in the patterns and concentrations of PFAAs in Osaka Bay and coastal waters of Western Japan indicate that the PFAAs in surface waters are influenced by sources from Keihanshin Metropolitan Area, mainly the Yodo River basin, and the dilution effect which naturally occurs during their transport to the Pacific Ocean. Graphical abstract: Highlights: PFAAs were analyzed in sediment and seawater samples from coastal waters of Western Japan. The highest concentration of ΣPFAA was determined in Ajifu Water way in Osaka. The ΣPFAA in seawater samples ranged between the LOQ and 53.4 ng L −1 . PFHxA was the most prevalent with the highest concentration of 37 ng L −1 . PFAAs in surface waters are influenced mainly by sources from the Yodo River basin.